HUBUNGAN TIPE INDUSTRI DAN UKURAN PERUSAHAAN TERHADAP CORPORATE SOCIAL RESPONSIBILITY (CSR) - Aisyah Aisyah (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2017)
Independent variables (industry type, company size) simultaneously or together have influence on the dependent variable (Corporate Social Responsibility (CSR)) where in table F with α: 0.05 obtained F table value of 2.76 and F count of 3.126 or Fcount> Ftable. 4. Partially the variable that has significant influence is the size of the company, where the value of T table: 1.699 smaller than the value Thitung: 3.365. 5. The influence of independent variable, that is industry type, and company size, to variable Y, that is Corporate Social Responsibility (CSR) is equal to 27,1% while the rest equal to 72,9% is influence sourced from other variable not examined